Immunogenic Cell Death and Immunomodulatory Effects of Cabozantinib - Scirocchi, Fabio; Napoletano, Chiara; Pace, Angelica; Rahimi Koshkaki, Hassan; Di Filippo, Alessandra; Zizzari, Ilaria Grazia; Nuti, Marianna; Rughetti, Aurelia (Frontiers in Oncology, 2021)
Cabozantinib (XL-184) is a multitarget Tyrosine Kinase Inhibitor (TKI) targeting receptor tyrosine kinases (RTKs) involved in oncogenesis and angiogenesis. It is currently standard therapy for medullary thyroid cancer (MTC), metastatic renal cell carcinoma (mRCC) and hepatocellular carcinoma (HCC). Combination of Cabozantinib with immunotherapy is now a standard treatment in metastatic renal cancer and its efficacy is being tested in ongoing clinical trial in prostate cancer patients. Here we report that Cabozantinib may exert an immunostimulatory role by inducing immunogenic stress of prostate cancer cells and modulating dendritic cells (DCs). Cabozantinib treatment arrested the cell cycle and triggered immunogenic cell death (ICD) in prostate cancer cells in vitro. Cabozantinib had a direct effect on DCs by the down-modulation of -catenin and change in migratory and costimulatory phenotype of the DCs. These results may suggest possible immunomodulatory effects induced by Cabozantinib that could be exploited to optimize patient tailored immunotherapeutic treatments.